An Analysis of Code Switching Used by Elvira Lianita in Gita Wirjawan’s Video Podcast Intitled “Rise Of Women: A Work in Progress - Ni Luh Putu Riska Agustiawati; Dewa Putu Ramendra; Putu Adi Krisna Juniarta (Jurnal Penelitian Mahasiswa Indonesia, 2022)
Code-switching has become part of bilingualism so that many people use code switching in daily conversations and this phenomenon has spread to all human life such as in politics, economics, education, social, culture and so on. Code switching as a language switching carried out by speakers from one language to another which use two or more languages in the conversation and switching of words, phrases, and sentences from two different grammatical systems across sentence boundaries in the same speech event in the various stituation. The present study aims to analyze code switching used by Elvira Lianita in Gita Wirjawan’s Video Podcast to describe the types of code-switching used by Elvira Lianita in Gita Wirjawan’s video podcast. This research was conducted trough descriptive qualitative. The source of the data is obtained from the Youtube channel, more precisely the one yutube channel owned by Gita Wirjawan. The subject of the study is Elvira Lianita who is the guest star in Gita Wirjawan's podcast video Elvira Lianita: Rise of Women, A Work in Progress. The instruments used to collect the data were checklist sheet. Based on the type of code switching contained in the conversation transcripts, they are classified into tag switching, intersentential switching, and intra-sentential switching and obtained 105 data and classified into three types of code-switching there are 9 or 8,5% data of tag switching, 77 or 73,3% data of intra- sentential switching, and 19 or 18% data of inter-sentential switching. Then, intra- sentential switching is the most frequently used by the speakers.